Complex Thought and the Recconection Of Knowledge - Alves, Eliana Aparecida; Bianchi, Cintia (Pontifícia Universidade Católica de São Paulo, 2021)
This article deals with the fragmentation of knowledge, hyper-specialization and the need to learn to reconnect knowledge within the teaching-learning process; it also deals with some polyvalent sciences that can favor the reconnection of knowledge and the need to reform thought, considering that complexity has as its sources, among others, three theories: the theory of information, the theory of cybernetics and the theory of systems. Therefore, to reform the thought that separates and fragments towards a thought that connects and reconnects: complex thinking is a thought that contextualizes and is capable of articulating knowledge.